Safety of intradiscal injection and biocompatibility of polyester amide microspheres in a canine model predisposed to intervertebral disc degeneration. Issue 4 (21st December 2015) - Willems, Nicole; Mihov, George; Grinwis, Guy C.M.; van Dijk, Maarten; Schumann, Detlef; Bos, Clemens; Strijkers, Gustav J.; Dhert, Wouter J.A.; Meij, Björn P.; Creemers, Laura B.; Tryfonidou, Marianna A.
Abstract: Repair of degenerated intervertebral discs (IVD) might be established via intradiscal delivery of biologic therapies. Polyester amide polymers (PEA) were evaluated for in vitro cytotoxicity and in vivo biocompatibility, and thereafter intradiscal application of PEA microspheres (PEAMs) in a canine model predisposed to IVD degeneration at long‐term (6 months) follow‐up. PEA extracts did not induce cytotoxicity in mouse fibroblast cells (microscopy and XTT assay), while a slight foreign body reaction was demonstrated by histopathology after intramuscular implantation in rabbits. Intradiscal injection of a volume of 40 µL through 26 and 27G needles induced no degenerative changes in acanine model susceptible to IVD disease. Although sham‐injected IVDs showed increased CAV1 expression compared with noninjected IVDs, which may indicate increased cell senescence, these findings were not supported by immunohistochemistry, biomolecular analysis of genes related to apoptosis, biochemical and histopathological results. PEAM‐injected IVDs showed significantly higher BAX/BCL2 ratio vs sham‐injected IVDs suggestive of an anti‐apoptotic effect of the PEAMs. These findings were not supported by other analyses (clinical signs, disc height index, T2 values, biomolecular and biochemical analyses, and IVD histopathology). PEAs showed a good cytocompatibility and biocompatibility. PEAMs are considered safe sustained release systems for intradiscal delivery of biological treatments. © 2015 The Authors. Journal of Biomedical Materials Research Part B: Applied Biomaterials published by Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 105B: 707–714, 2017.